The Movimento Autonomista Bergamasco and the Lega Nord: continuities and discontinuities. Issue 3 (1st March 2018) - Newth, George
Abstract : Studies of the Lega Nord (Northern League) have tended either to ignore the existence of earlier movements for regional autonomy in the 1950s – such as the Movimento Autonomista Bergamasco – or, on the contrary, assume continuities between the two movements at the expense of analysis of the significant discontinuities. This article argues that neither approach has been successful in capturing the importance of precursors to leghismo and that a more nuanced analysis is required. Focusing on the Movimento Autonomista Bergamasco (MAB) in its various incarnations between 1947 and 1970, I argue that the Bergamascan autonomists of the post-war period in many ways laid the foundations for Umberto Bossi's Lega Nord; however, it is historically inaccurate to claim a direct line of continuity between mabismo and leghismo due to the differing contexts in which each movement operated: the critical junctures of the post-war era and post-tangentopoli respectively. What emerges from a closer analysis of the relationship between the two movements, as mabismo evolved into leghismo in the 1980s is a picture of regional autonomism distancing itself from the ideal of national unity and being increasingly drawn to secessionism. Italian summary: Gli studi sulla Lega Nord hanno avuto la tendenza di ignorare l'esistenza di precedenti movimenti per l'autonomia regionale negli anni '50 – come il Movimento Autonomista Bergamasco – o, al contrario, di presupporre una progressione fra i due movimenti a scapito di un'analisi che mostra discontinuità significative. Questo articolo sostiene che nessuno dei due approcci ha avuto successo nel catturare l'importanza dei precursori del leghismo, e che è necessaria un'analisi che tenga conto delle varie sfumature. Concentrandomi sul Movimento Autonomista Bergamasco (MAB) nelle sue varie incarnazioni tra il 1947 e il 1970, sostengo che gli autonomisti bergamaschi del dopoguerra in un certo senso hanno posto le basi per la Lega Nord di Umberto Bossi; tuttavia, sarebbe storicamente inaccurato rivendicare una linea diretta di continuità tra 'mabismo' e 'leghismo' a causa dei diversi contesti in cui operava ciascun movimento: rispettivamente i momenti critici dell'era del dopoguerra e post-tangentopoli. Ciò che emerge da un'analisi più approfondita del rapporto tra i due movimenti, come il 'mabismo' evoluto poi in 'leghismo' negli anni '80, è un quadro dell'autonomia regionale che si allontana dall'ideale dell'unità nazionale e si fa sempre più attratto dal secessionismo.